Uncommon etiology of chronic wheeze - Varuna Jethani; Rakhee Sodhi Khanduri; Ankit Aggarwal; Suchita Pant (Indian Journal of Respiratory Care, 2019)
Endobronchial tuberculosis (TB) refers to TB infection of the tracheobronchial tree. We report the case of a 62-year-old immunocompetent patient of chronic cough with normal X-ray. She did not have any systemic complaints suggestive of TB. Her diagnosis was made when she underwent bronchoscopy to look for any endobronchial cause of cough. It revealed complete caseation in the airways. Microscopically and pathologically, it was confirmed to be tubercular. The patient improved clinically on antitubercular therapy.